EMPOWERING OLDER ADULTS AT THE NEIGHBORHOOD LEVEL: DIVERSE MODELS FOR DIVERSE POPULATIONS. (11th November 2018) - Ring, L; Glicksman, A; Graham, C
Abstract: This presentation will focus on two studies conducted in Philadelphia designed to explore innovative community based models for aging in place. The first study is an evaluation of the Friends in the City Plus (FitC+) program, which integrates formal LTSS into a Village type model. A survey of FitC+ members identified three key elements of the program's success: 1) fostering socialization and connection building among peers, 2) opportunities for member empowerment as program stakeholders, and 3) a "one stop shop" for access to supportive services. Utilizing these findings, the second study identifies ways that other neighborhood level programs prioritize and address these issues. Interviews were conducted with 8 different organization types (e.g. NORC, Age-friendly), which serve different populations. Outcomes from this study to be discussed include an analysis of the variation among programs, and the development of a "best practices" manual to assist other communities in sustaining their own efforts.